DISTRIBUSI UKURAN BUTIR MATRIKS BREKSI GUNUNGAPI DI DAERAH LOMBOK TIMUR, NUSA TENGGARA BARAT - -, Sigit Maryanto (Bulletin of Scientific Contribution, 2009)
Volcanic rock units of the Kalipalung, Kalibabak, and Lekopiko Formations are well cropped out at East Lombok area, composed predominantly of volcanic breccias. Grainsize analysis of selected volcanic breccias matrix show a similarity characters on the Kalipalung and Kalibabak Formation. On the other hand, a real difference founded between these formations with the Lekopiko Formation.